GNPNAT1 is a potential biomarker correlated with immune infiltration and immunotherapy outcome in breast cancer - Yuan, Renjie; Zhang, Yulu; Wang, Yange; Chen, Hongling; Zhang, Ruiming; Hu, Zhiyuan; Chai, Chengsen; Chen, Tingmei (Frontiers in Immunology, 2023)
Background: Glucosamine 6-phosphate N-acetyltransferase (GNPNAT1) is a crucial enzyme involving hexosamine biosynthesis pathway and is upregulated in breast cancer (BRCA). However, its biological function and mechanism on patients in BRCA have not been investigated. Methods: In this study, the differential expression of GNPNAT1 was analyzed between BRCA tissues and normal breast tissues using the Cancer Genome Atlas (TCGA) database and Gene Expression Omnibus (GEO) database, which was validated by quantitative real-time polymerase chain reaction, Western blot and immunohistochemistry. Then, the potential clinical value of GNPNAT1 in BRCA was investigated based on TCGA database. Functional enrichment analyses, including Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, Gene Set Variation Analysis, were performed to explore the potential signaling pathways and biological functions involved in GNPNAT1 in BRCA. Tumor immune infiltration was analyzed using ESTIMATE, CIBERSORT and TISIDB database; and immune therapy response scores were assessed using TIDE. Finally, Western blot, Cell counting kit-8 and Transwell assay were used to determine the proliferation and invasion abilities of breast cancer cells with GNPNAT1 knockdown. Results: GNPNAT1 was up-regulated in BRCA tissues compared with normal tissues which was subsequently verified in different cell lines and clinical tissue samples. Based on TCGA and GEO, the overexpression of GNPNAT1 in BRCA contributed to a significant decline in overall survive and disease specific survive. Functional enrichment analyses indicated that the enriched pathways in high GNPNAT1 expression group included citrate cycle, N-glycan biosynthesis, DNA repair, and basal transcription factors. Moreover, the overexpression of GNPNAT1 was negatively correlated with immunotherapy response and the levels of immune cell infiltration of CD8+ T cells, B cells, natural killer cells, dendritic cells and macrophages. Knockdown of GNPNAT1 impairs the proliferation and invasion abilities of breast cancer cells. Conclusion: GNPNAT1 is a potential diagnostic, prognostic biomarker and novel target for intervention in BRCA.